Measurement of hadron and lepton-pair production at 161 GeV <√s< 172 GeV‘at LEP - Dova, María Teresa (1997)
We report on measurements of e+e− annihilation into hadrons and lepton pairs. The data have been taken with the L3 detector at LEP at center-of-mass energies between 161 GeV and 172 GeV. In a data sample corresponding to 21.2 pb−1 of integrated luminosity 2728 hadronic and 868 lepton-pair events are selected. The measured cross sections and leptonic forward-backward asymmetries agree well with the Standard Model predictions.